Targeting the Wnt/β-Catenin Signaling Pathway as a Potential Therapeutic Strategy in Renal Tubulointerstitial Fibrosis - Li, Shan-Shan; Sun, Qian; Hua, Meng-Ru; Suo, Ping; Chen, Jia-Rong; Yu, Xiao-Yong; Zhao, Ying-Yong (Frontiers in Pharmacology, 2021)
Wnt/β-catenin signaling pathway plays important roles in embryonic development and tissue homeostasis. Wnt signaling is induced and β-catenin is activated, which is associated with the development and progression of renal fibrosis. Wnt/β-catenin controls the expression of a wide variety of downstream mediators such as snail1, twist, matrix metalloproteinase-7, plasminogen activator inhibitor-1, transient receptor potential canonical 6 and renin-angiotensin system components in epithelial cells, fibroblast and macrophages. In addition, Wnt/β-catenin is usually intertwined with other signaling pathways to promote renal interstitial fibrosis. Actually, in view of the crucial of Wnt/β-catenin signaling in renal fibrogenesis, blocking this signaling may be beneficial for renal interstitial fibrosis. There are several antagonists of Wnt signaling, including soluble Fzd-related proteins, the family of Dickkopf 1 proteins, Klotho and Wnt inhibitory factor-1, which negatively control Wnt activation. Furthermore, numerous emerging small-molecule β-catenin inhibitors cannot be ignored in the prevention and treatment of renal fibrosis. Moreover, we reviewed the knowledge focusing on antifibrotic effects of natural products commonly used in kidney disease by inhibiting Wnt/β-catenin signaling pathway. Therefore, in this review, we summarize recent advances the regulation, downstream targets, role and mechanisms of Wnt/β-catenin signaling in the pathogenesis of renal fibrosis. We also discuss the therapeutic potential of targeting this pathway for the treatment of renal fibrosis. This may shed new sights into effective treatment strategies for the prevention and treatment of renal fibrosis.